Assessing the Effects of Stocking Density on Turkey Tom Health and Welfare to 16 Weeks of Age - Beaulac, Kailyn; Schwean-Lardner, Karen (Frontiers in Veterinary Science, 2018)
Four levels of turkey tom SD (30, 40, 50, and 60 kg/m2) were evaluated in two 16 week trials (n=2,868 Nicholas Select). Poults were allocated to one of eight large independently ventilated rooms per trial (6.71 x 10.06 m) based on final predicted body weight. Room temperature, humidity, carbon dioxide and ammonia concentration were recorded throughout the trial; ventilation was adjusted to equalize air quality across treatments. Mobility (gait score, scale 0-5) was recorded at 12 and 16 weeks (20 birds per replicate). Footpad lesion score (scale 0-4), feather condition (scale 1-4) and cleanliness scores (scale 1-4) were recorded at 10 (Trial 2 only), 12, and 16 weeks of age (20 birds per replicate). Aggressive injury incidence was recorded daily for Trial 2 only. Stress (heterophil/lymphocyte ratio) was evaluated at 4, 12, and 16 weeks of age (15 birds per replicate). Behaviour was recorded and scan sampled (field of view) at 12 (Trial 1 only), 14, and 16 weeks. Data were analyzed using regression analysis (linear, Proc Reg; quadratic, Proc RSReg) for relationships between the variables and SD. Differences were considered significant when p≤0.05. Mobility and footpad lesions were unaffected at 12 weeks of age, but negatively affected by increasing SD (linear) at 16 weeks. Feather condition and cleanliness decreased linearly as SD increased at week 10, 12, and 16. The incidence of aggressive damage was significantly higher as SD increased during week 4-8 (quadratic). Heterophil/lymphocyte ratios increased linearly at 4 weeks and followed the same trend at 12 weeks. Behaviour was impacted at 12 weeks of age with standing behaviour showing a quadratic response, and walking and total disturbance showing a linear decrease as SD increased. At 14 weeks of age resting, preening, and comfort behaviours demonstrated a linear increase, while walking and strutting decreased linearly with increasing SD. Finally, at 16 weeks of age resting, standing, walking, feeding, and total disturbance responded quadratically while preening behaviour increased linearly with increasing SD. These results suggest that increasing SD negatively impacts bird health and wellbeing through decreased mobility, increased footpad lesions, poorer feather condition and cleanliness, and changes in behaviour.